FATIGUE CRACK PROPAGATION TEST AND SIMULATION ANALYSIS OF CAST E-GRADE STEEL CT SPECIMEN - WANG Chao; ZHU Tao; XIAO ShouNe; LIU YuJie; YANG Bing; YANG GuangWu; YIN MinXuan; XU JingTao (Jixie qiangdu)
In order to accurately obtain the fracture mechanics parameters of the cast E-grade steel material,and to study the crack propagation law and influencing factors of material,a fatigue crack growth test of the CT specimens of the cast E-grade steel was carried out. The Paris formula was used for characterization. Taking the crack growth calculation model of CT samples as an example,the fatigue crack growth length and load cycle period results of 5 groups of samples were calculated by using the M-integral numerical method. The relative error was within 10%,which had better consistency. Through further comparison and analysis of the reasons for the error between the test and the simulation,it is shown that the load amplitude is the main error factor,and the initial crack position,propagation rate parameters,and crack length parameters have little effect,so as to provide a reference for the prediction of three-dimensional fatigue crack propagation rules for complex structures.